Characterization and Physical and Biological Properties of Tissue Conditioner Incorporated with Carum copticum L. (12th August 2021) - Hejazi, Maryam; Zareshahrabadi, Zahra; Ashayeri, Sepideh; Saharkhiz, Mohammad Jamal; Iraji, Aida; Alishahi, Mohsen; Zomorodian, Kamiar
Abstract : Aim . One of the main problems in dentistry is the injury caused by the long-term application of an ill-fitting denture. The existence of multiple microorganisms along with the susceptibility of the tissue conditioners to colonize them can lead to denture stomatitis. This study is aimed at developing a tissue conditioner incorporated with Carum copticum L. ( C. copticum L. ) for the effective treatment of these injuries. Materials and Methods . The Carum copticum L. essential oil composition was determined by gas chromatography-mass (GC-mass) spectrometry. The antimicrobial activity of the essential oil against the standard strains of bacterial and fungal species was determined by broth microdilution methods as suggested by the Clinical and Laboratory Standards Institute (CLSI). The physical and chemical properties of the prepared tissue conditioner were investigated by viscoelasticity, FTIR assays, and the release study performed. Furthermore, the antibiofilm activity of the Carum copticum L. essential oil-loaded tissue conditioner was evaluated by using the XTT reduction assay and scanning electron microscopy (SEM). Results . The main component of the essential oil is thymol, which possesses high antimicrobial activity. The broth microdilution assay showed that the essential oil has broad activity as the minimum inhibitory concentration was in the range of 32-128  μ g mL -1 . The viscoelasticity test showed that the essential oil significantly diminished the viscoelastic modulus on the first day. The FTIR test showed that Carum copticum L. essential oil was preserved as an independent component in the tissue conditioner. The release study showed that the essential oil was released in 3 days following a sustained release and with an ultimate cumulative release of 81%. Finally, the Carum copticum L . essential oil exhibited significant activity in the inhibition of microbial biofilm formation in a dose-dependent manner. Indeed, the lowest and highest amounts of biofilm formation on the tissue conditioner disks are exhibited in the Streptococcus salivarius and Candida albicans by up to 22.4% and 71.4% at the 64  μ g mL -1 concentration of C. copticum L. with a statistically significant difference (P < 0.05 ). Conclusion . The obtained results showed that the Carum copticum L. essential oil-loaded tissue conditioner possessed suitable physical, biological, and release properties for use as a novel treatment for denture stomatitis.